The Spiritual Motivation from Az-Zarnuji’s View as a Management Strategy for Enhancing Students’ Aqidah Akhlaq Learning Achievement - Siti Nukhana; Ach. Syaikhu; Dhevin Puspita MQ; Akhmad Rudi Masrukhin Masrukhin (Al-Qalam Institue, 2026)
This study aims to examine the influence of spiritual motivation based on Al-Zarnuji’s perspective on students’ Aqidah Akhlaq learning achievement, while integrating the educational management dimension of instructional supervision as a mediating context. A quantitative correlational design was employed, involving 88 Grade X students selected through total sampling. Data were collected using a spiritual motivation questionnaire (initially 40 items, reduced to 13 after validity testing) and documentation of semester scores. Data were analyzed using Pearson correlation and simple linear regression. The results showed a positive relationship between spiritual motivation and learning achievement (r = 0.386), indicating a low to moderate correlation. Regression analysis revealed a positive effect of spiritual motivation on achievement (Y = 69.99 + 0.27X). These findings imply that spiritual motivation contributes meaningfully to academic performance, though its influence remains moderate. From an educational management perspective, the results underscore the importance of integrating instructional supervision and curriculum planning to systematically embed Al-Zarnuji’s spiritual motivation values into the teaching of Aqidah Akhlaq. This study offers practical implications for Islamic school administrators in designing motivation-based academic policies. .